EOQ Model versus (Q,r) Model: Case Study of a Company's Inventory in Londrina, Paraná, Brazil - Cainan Kobo Oliveira; Paulo Laerte Natti; Erica Regina Takano Natti; Eliandro Rodrigues Cirilo; Neyva Maria Lopes Romeiro (Semina: Ciências Exatas e Tecnológicas)
This article presents mathematical and statistical methods applicable to inventory management. Inventory analysis using ABC curves is used to identify priority items, the most expensive items, and those with the highest turnover (demand). Based on this information, it is possible to determine, through inventory control models, the optimal order quantity and frequency that minimize the total storage costs of these items. Using the Economic Order Quantity (EOQ) model and the (Q, r) model, inventory control models, the minimization of a company's inventory costs in Londrina, Paraná, Brazil was simulated. The comparison of the results provided by the models was discussed. Specifically, it was observed that for some inventory items, it would theoretically be possible to achieve savings margins of over 50% on inventory expenses for this company.